Evaluating the application of front-of-package labelling regulations to menu labelling in the Canadian restaurant sector using menu food label information and price (Menu-FLIP) 2020 data - Hayun Jeong; Yahan Yang; Christine Mulligan; Mary R L'Abbé (Cambridge University Press, 2024)
Abstract Objective: To evaluate the application of front-of-package (FOP) labelling regulations to menu labelling in the Canadian restaurant sector by assessing the proportion of menu items that would be required to display the 'high-in' FOP symbol if the policy were extended to the restaurant sector. Design: Nutrition information of 18 760 menu items was collected from 141 chain restaurants in Canada. Menu items were evaluated using the mandatory FOP labelling regulations promulgated in Canada Gazette II by Health Canada in July of 2022. Setting: Chain restaurants with ≥20 establishments in Canada. Participants: Canadian chain restaurant menu items including beverages, desserts, entrées, sides and starters. Results: Overall, 77 % of menu items in the Canadian restaurant sector would display a 'high-in' FOP symbol. Among these menu items, 43 % would display 'high-in' one nutrient, 54 % would display 'high-in' two and 3 % would display 'high-in' all three nutrients-of-concern. By nutrient, 52 % were 'high-in' sodium, and 24 and 47 % were 'high-in' total sugars and saturated fat, respectively. Conclusions: Given the poor nutritional quality of restaurant foods, the current regulations, if applied to restaurant foods, would result in most menu items displaying a FOP symbol. Therefore, expanding the Canadian FOP labelling regulations to the restaurant sector can be key to ensuring a healthy food environment for Canadians. Furthermore, menu labelling along with other multi-faceted approaches such as reformulation targets are necessary to improve the dietary intake of Canadians from restaurant foods.